Comparison of twice refocused spin echo versus stimulated echo diffusion tensor imaging for tracking muscle fibers. Issue 3 (19th February 2014) - Noehren, Brian; Andersen, Anders; Feiweier, Thorsten; Damon, Bruce; Hardy, Peter
<x xml:space="preserve">Abstract</x> Purpose To compare the precision of measuring the pennation angle and fiber length in the vastus lateralis (VL) using two distinctly different diffusion tensor imaging (DTI) sequences. Materials and Methods We imaged the thigh of 10 normal subjects on a 3T magnetic resonance (MR) imager with twice refocused spin echo (TRSE) and stimulated echo (STEAM) DTI‐MRI techniques. Both techniques took the same total acquisition time and employed the same diffusion weighting and gradient directions. Using the diffusion tensor images produced by each sequence, muscle fiber bundles were tracked from the aponeurosis by following the first eigenvector of the diffusion tensor. From these tracks we calculated the pennation angle and fiber length. Results The STEAM acquisition resulted in significantly higher signal‐to‐noise ratio (SNR), lower apparent diffusion coefficient (ADC), higher fractional anisotropy (FA) values, and longer fibers than TRSE. Although no difference in the pennation angle between the two acquisitions was found, the TRSE sequence had a significantly greater within‐subject dispersion in the pennation angle of tracked fibers, which may indicate a reduction in the coherence of fiber bundles. Conclusion DTI of muscle using a STEAM acquisition resulted in significant improvements in the SNR and FA, resulting in tracking a larger number of muscle fiber bundles over longer distances and with less within‐subject dispersion. J. Magn. Reson. Imaging 2015;41:624–632. © 2014 Wiley Periodicals, Inc.